Rain attenuation analysis using synthetic storm technique in Malaysia - Lwas, Ali K; Islam, Md Rafiqul; Chebil, Jalel; Habaebi, Mohamed Hadi; Ismail, Ahmad Faris; Zyoud, Al-Hareth; Dao, Hassan (IOP Publishing, 2013)
Generated rain attenuation time series plays an important role for investigating the rain fade characteristics in the lack of real fade measurements. A suitable conversion technique can be applied to measured rain rate time series to produce rain attenuation data and be utilized to understand the rain fade characteristics. This paper focuses on applicability of synthetic storm technique (SST) to convert measured rain rate data to rain attenuation time series. Its performance is assessed for time series generation over a tropical location Kuala Lumpur, in Malaysia. From preliminary analysis, it is found that SST gives satisfactory results to estimate the rain attenuation time series from the rain rate measurements over this region.